1998
DOI: 10.1103/physrevc.58.2292
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence of pion double charge exchange

Abstract: The energy dependence of forward angle pion double charge exchange is calculated in the energy range of 0-250 MeV. The most striking feature is a peak around 40 MeV which is in excellent agreement with the data when distorted waves obtained from a realistic optical model are used. Two possible short-range corrections to the reaction mechanism are addressed. ͓S0556-2813͑98͒07410-X͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…The energy dependence of the forward angle cross section for pion-nucleus double charge exchange (DCX) reactions has been shown to contain important information on the fundamental pion-nucleon charge exchange process and has been investigated extensively both experimentally [1,2,3] and theoretically [4,5]. See Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The energy dependence of the forward angle cross section for pion-nucleus double charge exchange (DCX) reactions has been shown to contain important information on the fundamental pion-nucleon charge exchange process and has been investigated extensively both experimentally [1,2,3] and theoretically [4,5]. See Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There have been controversial theoretical explanations of this peak. While some authors [2] have claimed that the peak is evidence for the existence of a dibaryon, we explained [3,4] this peak as the consequence of pion distortion based on a two-step sequential process which involves nucleons solely. It has been also shown that the energy dependence of the forward transition of DCX is sensitive to the configuration mixing [4].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of present work is to extend our previous studies [3,4] to medium mass nuclei, for which calculations are rare. To be specific, we study the DCX reactions 56 Fe(π…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, attempts were made [17], [18] to explain the peaks qualitatively by nuclear medium effects, but no explanation based on conventional nuclear physics exists, however, for the whole set of data on DCX, and, in particular, for nuclei with N = Z. A series of experiments in search of the d ′ has been performed at JINR [19], [20] and at TRIUMF [21], [22], where the DCX π + + 4 He → pppp π − was measured.…”
Section: ′ -Resonancementioning
confidence: 99%